Challenges and challenges of a rural organization: strict coupling/loose coupling (Revista de Investigaciones Universidad del Quindío, 2022)
The case of a rural organization "Chocolates Finos y Derivados El Yagual" dedicated to the elaboration of artisanal type chocolate is presented. The objective of the research was to describe the challenges they faced when adding value to cocoa. For observation, the Theory of Autopoietic Social Systems that distinguishes between system/environment was drawn as the explanatory theoretical framework coupled to the methodology. The field work involved conducting in-depth interviews with key informants of the organization, to whom a content analysis was carried out using the Atlas ti version 22 assisted platform as a tool. The results indicate that the main challenges that the rural organization faced, they were influenced by the selective inability of the political system to not be able at times to distinguish the demands of the organization system, with lax. One of the main challenges was the consolidation of knowledge around the added value of cocoa, strict control, which broadened the organization's expectations.
Keywords: Conflict of interests; second order observation; informal organization; Artisan chocolate; Lhumann; Communication